Neuroimaging abnormalities, neurocognitive function, and fatigue in patients with hepatitis C. Issue 1 (February 2015) - Thames, April D.; Castellon, Steven A.; Singer, Elyse J.; Nagarajan, Rajakumar; Sarma, Manoj K.; Smith, Jason; Thaler, Nicholas S.; Truong, Jonathan Hien; Schonfeld, Daniel; Thomas, M. Albert; Hinkin, Charles H.
Abstract : Objective: This study examined neurologic abnormalities (as measured by proton magnetic resonance spectroscopy imaging and diffusion tensor imaging), neurocognitive performance, and fatigue among a sample of adults with hepatitis C virus (HCV). We hypothesized that HCV+ individuals would demonstrate structural brain abnormalities and neurocognitive compromise consistent with frontostriatal dysfunction as well as increased fatigue compared to controls. Method: Participants were 76 individuals diagnosed with HCV and 20 controls who underwent a comprehensive neurocognitive evaluation and clinical assessments. A subset of the HCV+ participants (n = 29) and all controls underwent MRI. Results: Individuals diagnosed with chronic HCV infection demonstrated greater fractional anisotropy in the striatum as well as greater mean diffusivity in the fronto-occiptal fasciculus and external capsule compared to HCV− controls. HCV+ participants also demonstrated lower levels of N -acetylaspartate in bilateral parietal white matter and elevations in myo -inosital (mI) in bilateral frontal white matter compared to HCV− controls (all p values < 0.05). HCV+ participants also demonstrated significantly poorer neuropsychological performance, particularly in processing speed and verbal fluency. HCV+ patients reported higher levels of fatigue than controls, and fatigue was significantly correlated with diffusivity in the superior fronto-occipital fasciculus, elevations in mI in frontal white matter, and overall cognitive performance. Conclusions: Our results suggest that HCV-associated neurologic complications disrupt frontostriatal structures, which may result in increased fatigue and poorer cognitive performance, particularly in those cognitive domains regulated by frontostriatal regions.